Optimal Water Temperature and Salinity for Production of Blue Swimming Crab, Portunus pelagicus 1st Day Juvenile Crab - Mhd, Ikhwanuddin; Mohamad N., Azra; Mir A.D., Talpur; Ambok B., Abol-Munafi; Mohammad L., Shabdin (AACL Bioflux, 2012)
A study was carried out to determine the optimal rearing conditions of the water temperature and salinity on the survival rate and molting of larvae stage until the 1st day juvenile crab (C1) of the blue swimming crab, Portunus pelagicus (Linnaeus, 1758). Trials were carried out at water temperature 30ºC with water salinity 30 ppt and low salinity 20 ppt, ambient water temperature between 24-28ºC with salinity 30 ppt and low salinity 20 ppt. Results of the present study shows that both water temperature and salinity significantly affected survival of the crab larvae. Replicates treated with water temperature at 30ºC with water salinity 30 ppt produced C1 juvenile with mean survival rate 0.25% ±0.21. The larvae rearing for all the other three treatments did not survive up to C1. The study shows that the zoea reached the megalopa stage in 13-14 days and reached the C1 stage in 16-17 days for the larvae rearing batch treated with water temperature at 30ºC and water salinity at 30 ppt. The study recommended that the optimal water temperature and salinity for the larvae rearing of P. pelagicus is 30ºC and 30 ppt.